The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1016/s0961-9534(97)10066-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating environmental consequences of producing herbaceous crops for bioenergy

Abstract: The environmental costs and benefits of producing bioenergy crops can be measured both in terms of the relative effects on soil, water, and wildlife habitat quality of replacing alternate cropping systems with the designated bioenergy system, and in terms of the quality and amount of energy that is produced per unit of energy expended. While many forms of herbaceous and woody energy crops will likely contribute to future biofuels systems, The Department of Energy's Biofuels Feedstock Development Program ( B F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
213
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(220 citation statements)
references
References 13 publications
2
213
0
3
Order By: Relevance
“…41 In addition to increasing soil carbon (C), growing switchgrass may increase wildlife habitat, increase landscape and biological diversity, increase farm revenues, and return marginal farmland to production. [45][46][47][48] Not harvesting some switchgrass each year would increase the habitat value for grassland bird species that require tall, dense vegetation structure. 47 …”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…41 In addition to increasing soil carbon (C), growing switchgrass may increase wildlife habitat, increase landscape and biological diversity, increase farm revenues, and return marginal farmland to production. [45][46][47][48] Not harvesting some switchgrass each year would increase the habitat value for grassland bird species that require tall, dense vegetation structure. 47 …”
Section: Ecosystem Servicesmentioning
confidence: 99%
“…Experiments funded principally by the United States Department of Energy over the past two decades have shown that switchgrass is also a model herbaceous species for bioenergy production because of its perenniality, wide geographic distribution, high nutrient use efficiency, relatively low fertilization requirements, high biomass yield potential, and compatibility with conventional farm practices [2,3]. In order for switchgrass to be used to generate electricity by cofiring with coal, a substantial amount of biomass would need to be produced in the area close to the generating plant.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that the annual nitrogen requirement of switchgrass is about half that required for maize (Zea mays L.) production, or between 70 and 100 kg ha À1 [3]. Optimizing the application of nitrogen spatially and temporally is important to reach desirable switchgrass biomass yields without jeopardizing water quality or economic returns in the process [4].…”
Section: Introductionmentioning
confidence: 99%
“…Perennial sorghum cropping systems offer agroecological benefits not present in annual row crop production such as increased soil organic carbon, reduced soil erosion, reduced inputs requirements, and higher net energy return [10][11][12][13][14]. Land use change could be minimized in such systems through the utilization of marginal croplands or abandoned grasslands.…”
Section: Introductionmentioning
confidence: 99%